179k views
2 votes
Evaluate 2(x + 1) - 3 when x = 6.
ОА. 5
ов. 8
Ос. 11
OD. 10

User Hiral
by
5.6k points

2 Answers

3 votes

Answer:

C. 11

Explanation:

Evaluate 2(x + 1) - 3 when x = 6.

2(x + 1) - 3 <== substitute 6 for x

2(6 + 1) - 3 <== distribute 2

2(6) + 2(1) - 3

12 + 2 - 3 <== add and subtract

14 - 3

11 <== answer

Hope this helps!

User Bobwienholt
by
5.2k points
2 votes

Hey there!

2(x + 1) - 3

= 2(6 + 1) - 3

= 2(7) - 3

= 14 - 3

= 11

OR

2(x + 1) - 3

= 2(6 + 1) - 3

= 2(6) + 2(1) - 3

= 12 + 2 - 3

= 14 - 3

= 11


Therefore, your answer is: 11


Good luck on your assignment & enjoy your day!



~Amphitrite1040:)

User Sohammondal
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.